Communication of Java Language in The Form of Transmigration Families in Kalimantan - Ngalimun (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research will focus on the use of Javanese communication related to the form of family greetings that can be seen from the completeness of its elements. Javanese communication forms of family greetings are divided into three, namely: complete greeting forms, incomplete greeting forms, and a combination of complete greeting forms and incomplete greeting forms. Whereas based on the meanings and meanings of language communication, the form of family greetings can be in the form of self-names, kinship terms, paraban, national titles, adjective transpositions, and beatings. Factors that influence Javanese communication in the form of family greetings are the position of parents towards their children viewed from various aspects of course higher, but related to the use of the form of greeting it turns out that its use often shows a respectful form of greeting. This can be related to the role of the first person as a parent whose obligation is to educate and direct their children to be good children, who have good manners and can respect others and also their own parents. Other things that affect the form of family greetings are the first person, second person, third person, the meaning of the speaker, the color of the emotion, the tone of the speech, the subject, speech sequence, form of discourse, speech facilities, speech scenes, speech environment, and linguistic norms. Abstrak Penelitian ini akan difokuskan pada penggunaan komunikasi bahasa Jawa yang berkaitan dengan bentuk sapaan keluarga yangdapat dilihat dari kelengkapan unsur-unsurnya. Komunikasi bahasa Jawa bentuk sapaan keluarga dibedakan menjadi tiga, yaitu: bentuk sapaan lengkap, bentuk sapaan tak lengkap, dan gabungan bentuk sapaan lengkap dan bentuk sapaan tak lengkap. Sedangkan berdasarkan makna dan artinya komunikasi Bahasa bentuk sapaan keluarga dapat berupa nama diri, istilah kekerabatan, paraban, gelar kebangsawaan, transposisi ajektif dan poyokan. Faktoryang mempengaruhi komunikasi Bahasa Jawa dalam bentuk sapaan keluargaadalah posisi orang tua terhadap anak-anaknya dilihat dari berbagai segi tentunya lebih tinggi, namun berkaitan dengan pemakaian bentuk sapaan ternyata sering sekali penggunaannya justru menunjukan bentuk sapaan yang hormat. Hal ini dapat dikaitkan dengan peran orang pertama sebagai orang tua yang salah satu kewajibannya adalah mendidik dan mengarahkan anak-anaknya agar menjadi anak yang baik, yang memiliki sopan santun dan dapat menghormati orang lain dan juga orang tuanya sendiri. Hal lain yang mempengaruhi bentuk sapaan keluarga adalah orang pertama, orang kedua, orang ketiga, maksud penutur, warna emosi, nada suasana bicara, pokok pembicaraan, urutan bicara, bentuk wacana, sarana tutur, adegan tutur, lingkungan tutur, dan norma kebahasaan. Kata kunci: bentuk sapaan, komunikasi Bahasa Jawa